A Survey of Models, Technologies and Trends in Decision Making with Internet of Things - You Ari Faeni (ITEJ (Information Technology Engineering Journals), 2019)
The development of IoT (internet of things) technology encourages increased use of smart devices and their supporting applications. The use of smart devices and applications that are growing rapidly and large will certainly produce large amounts of data and information. The next challenge is how to use the data and information generated to help people solve various problems that exist and improve the quality of human life. Data is analyzed into information, knowledge and in the end it will be used to make decisions. With all the features offered by IoT, decision making is expected to be easier and more precise, according to the expected goals. This paper will discuss the IoT architecture and decision-making framework with IoT. Furthermore, it provides an overview of the models, technology and development of the decision making process with IoT based on previously published papers (journals and conferences). The main purpose of making this paper is to provide insights for researchers about decision making with IoT.